Effect of timing and duration of grazing of growing cattle in the West African Sahel on diet selection, faecal output, eating time, forage intake and live-weight changes and nutrition and performance of cattle - Ayantunde, Augustine A.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Keulen, H. van; Udo, H.M.J.; Chanono, M. (2001)
Sixty-four Azawak male weaned calves were allotted to eight treatments (T) in two trials to study the effect of timing (day or day-and-night) and duration of grazing on diet selection, faecal output, eating time, forage intake and weight changes. Grazing time during the day was 6 h for T 1, 2 and 3; 9 h for T 4, 5 and 6; and 12 h for T 7 and 8. Night grazing time was 0 h for T 1, 4 and 7; 3 h for T 2, 5 and 8; and 6 h for T 3 and 6. The trials were conducted from July 1995 to May 1996 covering the wet (WS), early dry (EDS) and late dry (LDS) seasons. Eight oesophageally fistulated steers were used in a cross-over design to sample the diet selected by day-grazers (D1) and by day-and-night-grazers during the day (D2) and at night (N2). Forage intake was determined from individual data on faecal output from all the calves and means of in vitro organic matter digestibility of extrusa of the fistulated steers. Water intake and eating time were measured in LDS. In WS there were no differences (P > 0?05) in the quality of the diet (extrusa) selected for D1, D2 and N2. In LDS, crude protein content for D1 was lower than for D2 (73 v. 79 (s.e. 2) g/kg dry matter, P < 0?05). In all seasons, faecal output and forage intake increased with total duration of grazing. Total time spent eating increased linearly with increasing total time allowed for grazing. These results suggest that allowing additional grazing time during the night leads to increased forage intake and consequently provides an opportunity for better animal production, especially in the dry season.